Penality at the Periphery: Deficits, Absences, and Negation - Brangan, Louise (Journal of contemporary criminal justice, 2023)
What might mean to reorientate the field of punishment and society so that we might be able to say it is democratizing, diversifying, and increasingly inclusive? If we wish to expand our knowledge of penal politics in particular, but also develop a more inclusive field of punishment and society, then we need to also examine the impact this ethnocentricity can have on shaping scholarship and debate within the periphery. The article contrasts two alternative readings of Irish penal politics to show how sometimes the concepts from the U.K. and U.S. penality can come to inflect studies of penal politics outside the mainstream. If we are to make an attempt at democratizing our knowledge, then it is as de Sousa Santos wrote, that the first struggle is often against ourselves. The article concludes with a brief critical discussion about who can speak for Southern and peripheralized places; where is even a southernized place; and if we are to democratize and diversify the study of penal politics, what role is there for our existing canon? I conclude that is not where we study, but how we study it.